What is intellectual property? (WIPO GenevaCH)
Deals briefly with topics such as: intellectual property; patents; trademarks; industrial design; geographic indication; and, copyright and related rights. Looks at the World Intellectual Property Organization.
Keywords: INTELLECTUAL PROPERTY